Application of Alkyletanolamide Surfactants Based on Nyamplung (Callophylum Inophylum L.) Seed Oil in Cream Base - Dita Auliya Nurfalah; Erin Ryantin Gunawan; Dedy Suhendra; Wahidah Fajrin (Universitas Pakuan, 2023)
Cream preparation is cosmetic preparation consisting of aqueous and oil phases that immiscible. Thus, a surfactant with hydrophilic and lipophilic groups is needed to reduce the interfacial tension between the two phases. Petroleum-based surfactants such as Triethanolamine (TEA) are often used in the cosmetic industry. In this study, however, alkyletanolamide surfactant synthesized from vegetable oil was used. Nyamplung, Callophylum inophylum L. (C. inophylum) oil is one of non-commercial vegetable oil that can be used as a substitute to produce surfactants. The aims of this study was to apply surfactant synthesized from C. inophylum oil on the cream preparation and to characterize the alkylethanolamide surfactant by determining the value of hydrophilic-lipophilic balance (HLB). Four different surfactant concentration, 1.5%, 2.0%, 2.5% and 0% were tested as base for the cream preparation. The best surfactant concentration for the cream-based formulation obtained in this study was 2.5% and the surfactant HLB value obtained was 14.40 indicating that alkyletanolamide surfactants can be applied to the oil-in-water (O/W) type of cream base formula.